Hubungan Faktor Risiko Individu dan Ergonomi dengan Kejadian Nyeri Punggung Bawah (Low Back Pain) pada Pengguna Game Online - Manda Sub Jakaria Koteng; Jacob M Ratu; Noorce Christiani Berek (Universitas Nusa Cendana, 2019)
Low Back Pain (LBP) is the pain experienced in the lower back muscles region. Sitting for a long time as that of online game users may cause such complaints. Other risk factors such as age, sex, BMI, and a longer time to play the game theoretically have a relationship with the incidence of LBP. This study aims to determine the relationship of individual factors and ergonomic factors to the incidence of LBP on the use of online games in Kupang. The study design was cross-sectional. The sample consisted of 38 online game users in Kupang and selected by using accidental sampling technique. Data analyzed by Chi-Square test with the significance of 95%. Result research indicated that individual factors that were age (p = 0.497), gender (p = 0.198), smoking (p = 0.547), and body mass index (p = 0.554) had no association with the incidence of LBP, while the ergonomic factors namely the duration of playing games (p = 0.007) and sitting position (p = 0.004) were related with LBP. Therefore, online game users should consider the duration of the game and sitting position applied in order to reduce LBP.